Analysis and Experimental Study of Automotive Synchronous Belt Transmission Noise - Guangchen Xu; Sisi Chen (Jixie chuandong)
In order to study the influence of tooth profile on the transmission noise of synchronous belt， the synchronous belt of ZA and RU type are taken as the research object. The vibration simulation model of two kinds of synchronous belts is carried out to solve the frequency response curve of transverse vibration. The vibration freqency response results are used as boundary element conditions to conduct the acoustic simulation analysis of two pulleys drive of the synchronous belt，the field frequency domain curve and noise distribution cloud image are obtained by simulation. A noise source identification device for synchronous belt transmission is built based on the sound array technology， and the influence of speed on the noise of two kinds of synchronous belt is tested. By comparing the simulation results with the experimental results， it is concluded that the resonance frequency of different tooth profiles is different in the resonance region. In the non-resonant region， the noise amplitude increases with the speed， and the transmission noise of RU type synchronous belt is about 4dB higher than that of ZA type synchronous belt.